5-Aminolevulinic Acid Multispectral Imaging for the Fluorescence-Guided Resection of Brain Tumors: A Prospective Observational Study - Charalampaki, Patra; Proskynitopoulos, Phileas Johannes; Heimann, Axel; Nakamura, Makoto (Frontiers in Oncology, 2020)
Fluorescence-guided surgery with five-aminolevulinic acid (5-ALA) is the state-of-the-art treatment of high-grade gliomas. However, intraoperative visualization of 5-ALA under blue light remains challenging, especially when blood covers the surgical field and thereby fluorescence. To overcome this problem and combine the brightness of visible light with the information delivered with fluorescence, we implemented multispectral fluorescence (MFL) in a surgical microscope, a technique that is able to project both information in real-time. We prospectively examined 25 patients with brain tumors. One patient was operated on two different lesions in the same setting. The tumors comprised: 6 glioblastomas, 4 ana-plastic astrocytomas, 1 anaplastic oligodendroglioma, 2 meningiomas, 11 metastatic tu-mors, 1 acoustic neuroma, and 1 ependymoma. The MFL technique with a real-time overlay of fluorescence and white light was compared intraoperatively to the classic blue filter. All lesions were clearly visible and highlighted from the surrounding tissue. The pseudocolor we chose was green, representing fluorescence, with the surrounding brain tissue remaining in its original color. When blood was covering the surgical field, orientation was easy to maintain. The MFL technique opens the way for precise and clear visualization of fluores-cence in real-time under white light. It can be easily used for the resection of all tumors ac-cumulating 5-ALA. Drawbacks of classic PpIX fluorescence such as hidden fluorescence, intraoperative changes could be overcome with the presence of additional white light in MFL technique.